2018
DOI: 10.1128/jb.00201-18
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to UV Irradiation Caused by Inactivation ofnurAandherAGenes in Thermus thermophilus

Abstract: NurA and HerA are thought to be essential proteins for DNA end resection in archaeal homologous recombination systems. , an extremely thermophilic eubacterium, has proteins that exhibit significant sequence similarity to archaeal NurA and HerA. To unveil the cellular function of NurA and HerA in, we performed phenotypic analysis of disruptant mutants of and with or without DNA-damaging agents. The and genes were not essential for survival, and their deletion had no effect on cell growth and genome integrity. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The mutL -lacking T. thermophilus HB8 strain was constructed as previously described (47). The wildtype, R27E, K78A, K78R, and K291A T. thermophilus mutL genes were ligated into the pMK18::HygΔKan plasmid (54,55) using XbaI and HindIII restriction sites. These plasmids were then transformed into the mutL -lacking T. thermophilus HB8 strain.…”
Section: Methodsmentioning
confidence: 99%
“…The mutL -lacking T. thermophilus HB8 strain was constructed as previously described (47). The wildtype, R27E, K78A, K78R, and K291A T. thermophilus mutL genes were ligated into the pMK18::HygΔKan plasmid (54,55) using XbaI and HindIII restriction sites. These plasmids were then transformed into the mutL -lacking T. thermophilus HB8 strain.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, two widely conserved archaeal genes, herA and nurA, have been implicated in HR since they are usually encoded in the same operon of Mre11 and Rad50 (Figure 9) [165][166][167] and the four genes are co-induced in response to UV irradiation [154,168]. Several studies have demonstrated that DNA resection requires the cooperation between the ATP-dependent Mre11-Rad50 and HerA-NurA complexes [169][170][171][172].…”
Section: Homologous Recombination In Archaeamentioning
confidence: 99%
“…In thermophilic archaea, herA and nurA are encoded in the same operon as rad50 and mre11 [400]. HerA and NurA have been shown to interact with each other both in vitro and in vivo [401]. The HerA-NurA ATP-dependent helicase-nuclease complex cooperates with Rad50-Mre11 to coordinate the repair of DSBs, although the mechanism has not yet been described in detail [400,[402][403][404].…”
Section: Hera-nuramentioning
confidence: 99%
“…Genetic studies have shown this is not the case in bacterial species Deinococcus radiodurans and Thermus thermophilus [ 406 ]; in the latter, deletion of nurA and herA has no effect on cell growth. Unexpectedly, T. thermophilus cells lacking nurA and herA show increased resistance to UV irradiation and MMC treatment [ 401 ].…”
Section: Dna Replicationmentioning
confidence: 99%